Omnichannel marketing strategy - V. I. Aleshnikova; T. A. Beregovskaya; E. V. Sumarokova (Вестник университета, 2019)
Scientific and practical problem, associated with the organization of longterm mutually beneficial relations between the seller and the buyer based on digital marketing has been examined. The concepts of the marketing channel as a single channel of sales, service, control, which uses diff ent formats, media tools; as well as omnichannel strategy based on the interests of the seller and the buyer have been сlarified. The results of a comparative analysis of multichannel and omnichannel strategies in marketing according to nine characteristics; author’s model “omnichannel marketing wheel” have been introduced in the article. The model reflects the specifics of the omnichannel marketing strategy. Seven main groups of elements, that provide the conditions for a «seamless» continuous mutually beneficial interaction between seller and customer, have been presented in this model.